PENGEMBANGAN KURIKULUM PAI DI RA AL-FADLILIYAH DARUSSALAM CIAMIS - Asep Samsul Umam; Melly Oktaviani; Tanto Aljauharie Tantowie (As-Sulthan Journal of Education, 2026)
This study aims to evaluate the implementation of the Islamic Religious Education (IRE) curriculum at RA Al-Fadliliyah Darussalam through field observations and comprehensive analysis of the curriculum's design, approach, objectives, materials, learning process, and evaluation. The results show that the implementation of the IRE curriculum at this RA has been carried out comprehensively and integratively, in accordance with the principles of early childhood education. The adopted curriculum design combines the Merdeka Curriculum, the CINTA-Based Curriculum, and pesantren characteristics, which focus not only on knowledge but also on the formation of morals and Islamic values.  The approach used is thematic-integrative and play-based learning, where religious values are internalized through daily routines, motor activities, games, stories, and projects. Flagship programs such as IQRA, prayer memorization, pesantren-based schools, and the adiwiyata curriculum demonstrate the institution's commitment to building religious character, love for the environment, and love for Indonesia. Overall, RA Al-Fadliliyah Darussalam has effectively implemented the PAI curriculum with consistent habits and a religious learning environment. Continuous evaluation also contributes positively to improving the learning design, so that this curriculum has had a positive impact on the religious and personal development of students.